Frequency and Temperature Dependences of Dielectric Dispersion and Electrical Properties of Polyvinylidene Fluoride/Expanded Graphite Composites. (9th December 2009) - Li, Yu Chao; Li, Robert Kwok Yiu; Tjong, Sie Chin
Abstract : A conductive nanofiller, expanded graphite (EG), was introduced into polyvinylidene fluoride (PVDF) by direct melt blending process. The electrical conductivity and dielectric properties of resulting PVDF/EG composites were investigated in a wide range of frequencies from10 2 to10 8 Hz. The dielectric dispersion and conductivity of the composite system exhibited a strong frequency dependence particularly in the vicinity of percolation threshold (Φ c = 6 vol%). Moreover, the dielectric permittivity tended to decrease with increasing frequency while the conductivity displayed a reverse trend. A large permittivity was found in the composite having EG content nearΦ c . Accordingly, percolation concept and biased random walk approach can be used to describe the carrier transport of percolating PVDF/EG system. The conductivity and permittivity of percolating PVDF/EG composites were observed to be temperature dependent.